Analisis Kebocoran Boiler Pipe Akibat Korosi pada Recovery Boiler 5 PT. ABC. - Ridwan Abdurrahman; Dedy Masnur; Abdul Rahman (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Riau, 2023)
Boiler is one component that is widely used in the energy generation industry and reactors. One of the main components of the boiler is the boiler pipe. In field activities, there was a leak in the boiler pipe which experienced corrosion and erosion of the walls of the pipe. This condition results in a decrease in power and capacity in the boiler. The purpose of this practical work is to observe the causes of damage to the boiler pipe, and provide recommendations for prevention due to damage to the boiler pipe. The methods used are: literature study, observation, interviews, and measurement. The results obtained: (1) The calculation results show that the value of the Reynolds number obtained is 16,032,025.86 (Re>4000, turbulent flow). (2) The cause of corrosion on the boiler pipe is due to liquid droplet impingment which is accompanied by an increase in flow velocity and the occurrence of two phases (steam and water) thereby accelerating depletion in the boiler.